The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1007/s10555-005-5135-2
|View full text |Cite
|
Sign up to set email alerts
|

Review of Growth Inhibitory Peptide as a Biotherapeutic agent for tumor growth, adhesion, and metastasis

Abstract: This review surveys the biological activities of an alpha-fetoprotein (AFP) derived peptide termed the Growth Inhibitory Peptide (GIP), which is a synthetic 34 amino acid segment produced from the full length 590 amino acid AFP molecule. The GIP has been shown to be growth-suppressive in both fetal and tumor cells but not in adult terminally-differentiated cells. The mechanism of action of this peptide has not been fully elucidated; however, GIP is highly interactive at the plasma membrane surface in cellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(75 citation statements)
references
References 74 publications
0
67
0
Order By: Relevance
“…It has been further demonstrated in vitro that GIP notably interrupted the migration and invasion of follicular thyroid cancer cells [37] . It has also been reported that GIP could inhibit 60% of the cell spreading and migration of MCF-7 tumor cells in culture assays [34] . Because integrins and ECM proteins are both involved in cell migration by modulating the fine balance between cell-to-contact, adhesion, and cell detachment, it was noteworthy that GIP was found capable of disrupting the interaction between receptors and binding proteins in such activities.…”
Section: Biological Activities Of Afp-derived Peptidesmentioning
confidence: 92%
See 2 more Smart Citations
“…It has been further demonstrated in vitro that GIP notably interrupted the migration and invasion of follicular thyroid cancer cells [37] . It has also been reported that GIP could inhibit 60% of the cell spreading and migration of MCF-7 tumor cells in culture assays [34] . Because integrins and ECM proteins are both involved in cell migration by modulating the fine balance between cell-to-contact, adhesion, and cell detachment, it was noteworthy that GIP was found capable of disrupting the interaction between receptors and binding proteins in such activities.…”
Section: Biological Activities Of Afp-derived Peptidesmentioning
confidence: 92%
“…Regarding cancer cell proliferation, GIP was found to inhibit growth in multiple BC cell lines in vitro and to inhibit cell-tocell contact inhibition overgrowth in cultured MCF-7 cells [33][34][35] . In addition, both full length AFP and GIP were both found capable of inhibiting platelet aggregation [36] , a process necessary for CTC survival in the bloodstream; this activity involved integrins α2β1, α5β1, and α2β3.…”
Section: Biological Activities Of Afp-derived Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhi Yao, 1,2 Academy of Military Medical Sciences (Beijing, China). The animals were maintained at our university under specific pathogen-free (SPF) conditions according to the guidelines of the Chinese Association for Laboratory Animal Care, using a laminar air-flow rack, and had continuous access to sterilized pelleted food and autoclaved water with a controlled light/dark cycle, temperature at 20 to 25°C, and 50% to 60% relative humidity with 15 fresh air changes per hour.…”
Section: Inhibition By Tyroserleutide (Ysl) On the Invasion And Adhesmentioning
confidence: 99%
“…It is crucial to control the invasion and metastasis of tumors in the treatment for cancer. GIP (growth inhibitory peptide) has been reported to inhibit the growth, adhesion, and metastasis of some tumors (2). RGD (Arg-Gly-Asp) and YIGSR (Tyr-Ile-GlySer-Arg) also showed the same effects on mouse melanoma (3,4).…”
Section: Introductionmentioning
confidence: 99%